Ensilado combinado de zapallo (Cucurbita maxima) con nacedero (Trichanthera gigantea) como inclusión no convencional en cerdos en la etapa de recría - Pincay Vélez, Jonathan Fernando (2024)
This research evaluated the combined use of silage made from squash (Cucurbita maxima) and nacedero (Trichanthera gigantea) as a non-conventional inclusion in pigs during the rearing stage. Twenty-four 42-day-old crossbred Landrace x PIC337 piglets were selected as the experimental units, distributed into three treatments with eight repetitions, subdivided into two groups (four females and four males), for a total of 24 observational units. A completely randomized 2x2 factorial design with a 5% alpha value was used. The control treatment (T0) consisted of commercial feed, T1 included 0.25 kg of silage, and T2 included 0.50 kg of silage. Each piglet was fed twice a day with the addition of silage for four weeks, and initial weight, weekly weight, and feed consumption were recorded. Data were analyzed using Statistix 10 (2020). The results showed significant differences between the treatments, with T1 achieving the highest values in productive parameters of final weight gain and final feed consumption (p<0.00) compared to T0. Plasma cortisol levels averaged 94.58 ng/mL, which is within the physiological range, and T1 demonstrated higher cost-benefit efficiency with a profitability of $0.17 per dollar invested. It is important to highlight that both T1 and T2 achieved favorable productive outcomes in piglets without affecting cortisol levels.